2020
DOI: 10.3389/fimmu.2020.00126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mesenchymal Stem Cell Therapy for Sepsis: A Randomized Controlled Porcine Study

Abstract: Background: Treatment with mesenchymal stem cells (MSCs) has elicited considerable interest as an adjunctive therapy in sepsis. However, the encouraging effects of experiments with MSC in rodents have not been adequately studied in large-animal models with better relevance to human sepsis. Objectives: Here, we aimed to assess safety and efficacy of bone marrow-derived MSCs in a clinically relevant porcine model of progressive peritonitis-induced sepsis. Methods: Thirty-two anesthetized, mechanically ventilated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
(53 reference statements)
0
27
2
Order By: Relevance
“…Although our work has shown that MSCs are effective in murine and swine septic shock models, improving survival, organ failure, and bacterial load, we did not observe any MSC impact on inflammatory secreted factors, unlike other studies 28,30 . Similarly, in a porcine sepsis model, Horak et al did not find any impact of BM‐MSCs on inflammation 31 . However, they did not observe either any beneficial effect of MSCs on organ failures, unlike us.…”
Section: Mscs and Sepsis Including The Context Of Covid‐19contrasting
confidence: 94%
See 1 more Smart Citation
“…Although our work has shown that MSCs are effective in murine and swine septic shock models, improving survival, organ failure, and bacterial load, we did not observe any MSC impact on inflammatory secreted factors, unlike other studies 28,30 . Similarly, in a porcine sepsis model, Horak et al did not find any impact of BM‐MSCs on inflammation 31 . However, they did not observe either any beneficial effect of MSCs on organ failures, unlike us.…”
Section: Mscs and Sepsis Including The Context Of Covid‐19contrasting
confidence: 94%
“…28,30 Similarly, in a porcine sepsis model, Horak et al did not find any impact of BM-MSCs on inflammation. 31 However, they did not observe either any beneficial effect of MSCs on organ failures, unlike us. Despite the report of contradictory results, a recent metaanalysis of 29 animal studies, including 1266 animals, demonstrated that MSC therapy was related to a significant lower mortality rate.…”
Section: Mscs and Sepsis Including The Context Of Covid-19contrasting
confidence: 73%
“…Regarding the safety and effectiveness of MSCs in the treatment of sepsis, phase 1 clinical trials have been conducted [43,44], but MSCs have not yet been used for the clinical treatment of sepsis. To our knowledge, a recent large-animal study [50], using the animal models of pigs, demonstrated that MSCs were not capable of reducing the mortality induced by sepsis. Concerning its small sample size, more large-animal studies are needed.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding the safety and effectiveness of MSCs in the treatment of sepsis, phase 1 clinical trials have been conducted [43,44], but MSCs have not yet been used for the clinical treatment of sepsis. To our knowledge, a recent large-animal study [53], using the animal models of pigs, demonstrated that MSCs were not capable of reducing the mortality induced by sepsis. Concerning its small sample size, more large-animal studies are needed.…”
Section: Discussionmentioning
confidence: 91%